Finite-size scaling study of non-equilibrium percolation: letter to the editor - Lironis, G.; Heermann, Dieter W.; Binder, Kurt (Journal of physics. A, Mathematical and theoretical, 1989)
Induced by phase separation in the lattice gas model a transient percolation phenomenon occurs for concentrations c exceeding a critical curve c (corr) p (T, t) which depends both on temperature T and on the time t passed after the quench to a state inside the miscibility gap. A finite-size scaling analysis of extensive Monte Carlo data is carried out to locate c (corr) p (T, t) and to show that the critical behaviour of this percolation transition is consistent with random percolation, contrary to previous suggestions.
Gesehen am 23.08.2017